LANGUAGE FUNCTIONS IN PUBLIC SERVICE ADVERTISEMENTS: GERAKAN LITERASI NASIONAL (GLN) - Setyowati, Ririn; Lubis, Indah Sari (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
Language serves as the communication tool whether it is verbal and non-verbal ways.  To understand the language intention, we have to know the function, then it is called as the language function. In this study, the language functions were conducted in Public Service Advertisements which entitled Gerakan Literasi Nasional (GLN). The objectives of the study were to find out the language functions presented in the advertisements of Gerakan Literasi Nasional and to describe the purposes of those advertisements in it. The theory proposed was Jakobson`s language function and the research design applied was Qualitative Content Approach (QCA). The data were obtained from two sorts of advertisement which had the same theme in spite of different sources. One was from SMK Budi Warman 1 Jakarta Timur and another one was from public government by Kemendikbud. The data were analyzed by Miles and Huberman`s concept within the procedure of discourse analysis. The findings of the study were 1) there were four types of language functions as referential, emotive, conative and poetic functions, and 2) the purposes of the advertisements in GLN were mainly to persuade and inform the viewers about the importance of literacy to improve their knowledge.